Recent advances in immunotherapy for gliomas: overcoming barriers and advancing precision strategies - Jabri, Abdullah; Mhannayeh, Abdulaziz; Taftafa, Bader; Alsharif, Mohamed; Sibai, Dania; Alsharif, Raghad; Abbad, Tasnim; Elsalti, Abdulrahman; Ahmed, Zara; Salma, Jahan; Khan, Mohammed Imran; Yaqinuddin, Ahmed (Frontiers in Immunology, 2026)
Gliomas, and particularly glioblastoma (GBM), remain among the most lethal primary brain tumors, with outcomes constrained by extensive intra tumor heterogeneity, a profoundly immunosuppressive tumor microenvironment (TME), and the restrictive nature of the blood–brain barrier (BBB). Although immunotherapies, including immune checkpoint inhibitors, chimeric antigen receptor (CAR) T and NK cells, and oncolytic virotherapy, have redefined treatment paradigms in other malignancies, their efficacy in gliomas has been modest, limited by low tumor mutational burden, antigenic plasticity, metabolic suppression, and therapy-associated immunosuppression. Recent advances in multi-antigen targeting, metabolic reprogramming, and innovative delivery strategies have enhanced preclinical efficacy, while the integration of emerging biomarkers such as ADAMTSL4, ACSS3, and radiomics-derived immune signatures offers opportunities for precision patient stratification. Converging developments in real-time molecular monitoring, spatial immunoprofiling, and rationally designed combination regimens hold the potential to recalibrate the glioma immune landscape, paving the way toward clinically impactful and durable immunotherapeutic responses.